Proceedings of the 2014 Conference on Empirical Methods in Natural Language Processing (EMNLP) 2014
DOI: 10.3115/v1/d14-1222
|View full text |Cite
|
Sign up to set email alerts
|

A Rule-Based System for Unrestricted Bridging Resolution: Recognizing Bridging Anaphora and Finding Links to Antecedents

Abstract: Bridging resolution plays an important role in establishing (local) entity coherence. This paper proposes a rule-based approach for the challenging task of unrestricted bridging resolution, where bridging anaphors are not limited to definite NPs and semantic relations between anaphors and their antecedents are not restricted to meronymic relations. The system consists of eight rules which target different relations based on linguistic insights. Our rule-based system significantly outperforms a reimplementation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(58 citation statements)
references
References 13 publications
0
55
0
3
Order By: Relevance
“…We started with a re-implementation of the state-ofthe-art rule-based method by Hou et al (2014), which did not achieve satisfactory performance when being applied to the ARRAU corpus. We found that the reasons for this lie in the different bridging annotations.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We started with a re-implementation of the state-ofthe-art rule-based method by Hou et al (2014), which did not achieve satisfactory performance when being applied to the ARRAU corpus. We found that the reasons for this lie in the different bridging annotations.…”
Section: Resultsmentioning
confidence: 99%
“…As a starting point, we adopt the approach by Hou et al (2014) and re-implement a rule-based system for full bridging resolution 1 . The system contains eight rules.…”
Section: Data Splitsmentioning
confidence: 99%
See 3 more Smart Citations